The role of intracellular pathways in the proliferation of human K562 cells mediated by muscarinic receptors - AYDIN OMAY, BANU; CABADAK, HÜLYA (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
Muscarinic acetylcholine receptors (mAChRs) are members of the superfamily of G protein coupled receptors (GPCRs). Muscarinic receptors are relatively abundant in the central nervous system and in the peripheral parasympathetic nervous system. Several studies have suggested that muscarinic receptors also mediate some cellular events in hematopoietic cells. K562 erythroleukemia cells contain muscarinic receptors M-2, M-3 and M-4, and activation of muscarinic receptors changes cell proliferation. We examined the effects of several compounds on cell proliferation in K562 erythroleukemia cells. These included a muscarinic receptor agonist carbachol (CCh), a protein kinase inhibitor staurosporine; the phospholipase C inhibitor U73122, the MEK 1-2 inhibitor UO126, the PI3-kinase inhibitor wortmannin, the Ca2+ chelators BAPTA/AM and 2-aminoethoxy-diphenylborate (2APB). In addition, we also investigated muscarinic receptor mediated protein kinase C (PKC) expression in K562 cells. CCh caused a decrease in DNA synthesis in K562 cells supplemented with 1% fetal bovine serum after starvation. Pre-treatment of K562 cells with U73122 and BAPTA/AM antagonized the inhibitory effect of CCh, suggesting that phospholipase C and intracellular calcium are involved in CCh-mediated inhibition of proliferation in K562 cells. Our data also suggest that the regulatory roles of protein kinase C and the MAPK/ERK pathways in K562 cell proliferation are independent of cholinergic activation. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Muscarinic receptors; Cell signaling; Atropine; Carbachol; PKC; Leukemia cell line; PROTEIN-KINASE-C; NONNEURONAL CHOLINERGIC SYSTEM; SIGNAL-TRANSDUCTION PATHWAYS; ACETYLCHOLINE-RECEPTOR; DNA-SYNTHESIS; CHICK HEART; EXPRESSION; CAMP; STIMULATION; SUBTYPES